An Analysis of The Influence of Brand Image, Price, and Instagram Digital Marketing on Consumer Purchasing Decision at PT. Sardana Indahberlian Motor - Aris Jona Pangaribuan; Wulan Dayu; Hendra Utama (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the influence of brand image, price, and digital marketing through Instagram social media on consumer purchasing decisions at PT. Sardana Indahberlian Motor. In the midst of competitive automotive industry competition, companies are required to optimize digital platforms and strengthen brand value. This study uses a quantitative approach and the determination of the number of samples for this study uses the Slovin formula so that a sample of 95 respondents is obtained and the collection uses a questionnaire with a Likert scale. The data analysis technique used is validity testing, reliability, and classical assumptions then multiple linear regression analysis with hypothesis testing using the t test and F test at α = 5% using SPSS software version 26. The results of the study indicate that partially, brand image and digital marketing have a significant effect on purchasing decisions. The price variable also shows a positive influence driven by the suitability between product quality and the value paid by consumers. Simultaneously, the three independent variables contribute significantly in shaping consumer purchasing decisions. Variations in purchasing decisions can be explained by variations in product quality, price, and promotion, which amount to 70% percent, while the remaining 30% is explained by other variables outside this study.